1998
DOI: 10.1046/j.1432-1327.1998.2570192.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic consequences of accumulating the common 4977‐bp mitochondrial DNA deletion

Abstract: Mutations and deletions in mitochondrial DNA (mtDNA) lead to a number of human diseases characterized by neuromuscular degeneration. Accumulation of truncated mtDNA molecules (∆-mtDNA) lacking a specific 4977-bp fragment, the common deletion, leads to three related mtDNA diseases : Pearson's syndrome; Kearns-Sayre syndrome; and chronic progressive external ophthalmoplegia (CPEO). In addition, the proportion of ∆-mtDNA present increases with age in a range of tissues. Consequently, there is considerable interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
121
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 23 publications
8
121
0
1
Order By: Relevance
“…Our finding is also biologically plausible, due to the fact that cancer cells are metabolically adapted for rapid growth and proliferation under conditions of low pH and oxygen tension, solid cancer cells generate energy by glycolysis in strong preference to oxidative phosphorylation (33)(34)(35). Furthermore, previous in vitro studies have suggested that mitochondrial protein synthesis is defective and the activity of cytochrome oxidase decreases when the proportion of the mtDNA 4977 mutation was greater than 60% in the cancer cell (23). The amount of the mtDNA 4977 mutation that accumulates may not be sufficient, by itself, to cause a significant defect or dysfunction in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding is also biologically plausible, due to the fact that cancer cells are metabolically adapted for rapid growth and proliferation under conditions of low pH and oxygen tension, solid cancer cells generate energy by glycolysis in strong preference to oxidative phosphorylation (33)(34)(35). Furthermore, previous in vitro studies have suggested that mitochondrial protein synthesis is defective and the activity of cytochrome oxidase decreases when the proportion of the mtDNA 4977 mutation was greater than 60% in the cancer cell (23). The amount of the mtDNA 4977 mutation that accumulates may not be sufficient, by itself, to cause a significant defect or dysfunction in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mtDNA 4977 mutation affects genes encoding 7 polypeptide components of the mitochondrial respiratory chain and 5 of the 22 tRNAs necessary for mitochondrial protein synthesis (23). Thus, the mutated mtDNA 4977 may represent a strong functional disadvantage, possibly thereby repressing the growth of cancer cells harboring deleted mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Single mtDNA deletions cause KSS, CPEO, or PS, whose affected tissues show impaired electron transport activity, ATP production, and mitochondrial protein synthesis [26,56,57]. Muscle biopsies from patients with KSS or CPEO show ragged-red fibers and cytochrome oxidase-negative fibers [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Although a specific deletion encompassing 4,977bp is commonly reported,6 single, large‐scale mtDNA deletions vary in size (between 1.3 and 10kb), removing a number of genes encoding both mt‐tRNAs and structural mRNAs 7, 8, 9, 10, 11. They are typically mutational events that occur during the replication/repair of the mitochondrial genome and are invariably heteroplasmic in human tissues ‐ a condition where both mutated and wild‐type mtDNA genomes coexist in the same cell.…”
mentioning
confidence: 99%
“…They are typically mutational events that occur during the replication/repair of the mitochondrial genome and are invariably heteroplasmic in human tissues ‐ a condition where both mutated and wild‐type mtDNA genomes coexist in the same cell. In postmitotic tissues, such as skeletal muscle, the proportion of deleted to wild‐type mtDNA must exceed a reported threshold (50–90%)9, 10, 11, 12, 13 for the expression of a biochemical defect, leading to a marked mosaicism between different fibers and well‐described cytochrome c oxidase (COX)‐deficient, ragged‐red fibers 13…”
mentioning
confidence: 99%